Politics in Action : Cases in Modern American Government - Wasserman, Gary (Houghton Mifflin Company, 2006)
This unique, engaging reader presents 13 case studies each presenting a familiar event in modern political history. The event is dissected to create a snapshot of the relative institutions, policymakers, and groups that influenced its development. Factors under consideration include individual political personalities, public opinion on national policy, the role of the media, and the impact of lobbyists. Politics in Action encourages students to take a critical approach to contemporary events and consider the impact of politics on everyday life